The psychological relationship between companies and freelancers: An empirical study of the commitment and the work-related expectations of freelancers - Stefan Süß; Markus Kleiner (Management Revue, 2007)
For some years now a tendency towards a more flexible shaping of employment has been observable. Little research, however, has been dedicated to the question of how relevant this is for the commitment of freelance employees. Therefore the present paper first reverts to the question as to whether - and if so, under what preconditions - freelancers are likely to feel commitment towards the company that employs them. Second, the paper identifies clusters of freelancers following their work-related expectations. On the basis of an empirical study among IT-freelancers it becomes clear that freelancers differ from permanent employees as regards their work-related expectations. Consequences for their felt commitment hence ensue. All in all it is mainly an affective commitment towards their company which they perceive.
Keywords: 650; commitment; flexible employment forms; freelanced employees; work-related expectations; Informationstechnik; Selbstständige; Unternehmensnetzwerk